2019
DOI: 10.1177/0003489419887406
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Readability of Online Information on In-Office Vocal Fold Injections

Abstract: Objectives: Vocal fold injection augmentations are increasingly being performed in the office setting on awake patients, as opposed to the operating room. These procedures thus require patient cooperation and education. As the Internet is a widely-used resource for patients, our aim was to assess the quality and readability of online resources on in-office awake vocal fold injections. Methods: An online Google search using the terms “office vocal fold injection medialization” and “awake vocal fold injection” w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…However, studies have shown that online PEMs are often written at a much higher literacy level [13][14][15][16]. Within the realm of otolaryngology-head and neck surgery (OHNS), several studies have revealed that online information on OHNS procedures and conditions are written above the recommended grade level and are lacking in terms of quality [17][18][19][20][21][22][23]. Since septoplasty is a common OHNS procedure, it is important that clinicians evaluate the information patients are accessing online about their surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that online PEMs are often written at a much higher literacy level [13][14][15][16]. Within the realm of otolaryngology-head and neck surgery (OHNS), several studies have revealed that online information on OHNS procedures and conditions are written above the recommended grade level and are lacking in terms of quality [17][18][19][20][21][22][23]. Since septoplasty is a common OHNS procedure, it is important that clinicians evaluate the information patients are accessing online about their surgery.…”
Section: Introductionmentioning
confidence: 99%
“…52 Three previous peer-reviewed publications of the senior author also used these three instruments. [14][15][16] Google was chosen as the search engine as it owns about 91% of the search engine market share. 54 Other search engines, like Yahoo and Bing, may have yielded slightly different results.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous publications by the senior author also used 50 websites with similar methodology. [14][15][16]37 Despite the current state of ISS website quality and readability, there are benefits associated with online resources. For instance, a large online community of patients diagnosed with ISS belongs to a Facebook group called "Living with Idiopathic Subglottic Stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…shown in Table 1. These formulas have been supporting researchers' studies for assessing and subsequently improving readability of assorted types of reading materials [26][27]. As its definition goes "… the level of ease or difficulty with which text material can be understood by a particular reader who is reading that text …" [28], readability is a relative concept which largely depends on the readers of the text.…”
Section: Readability Measurementmentioning
confidence: 92%